Distribution of ABL and BCR genes in cell nuclei of normal and irradiated lymphocytes - Kozubek, S; Lukásová, E; Rýznar, L; Kozubek, M; Lisková, A; Govorun, R D; Krasavin, E A; Horneck, G (Blood, 1997)
Using dual-color fluorescence in situ hybridization (FISH) combined with two-dimensional (2D) image analysis, the locations of ABL and BCR genes in cell nuclei were studied. The center of nucleus-to-gene and mutual distances of ABL and BCR genes in interphase nuclei of nonstimulated and stimulated lymphocytes as well as in lymphocytes stimulated after irradiation were determined. We found that, after stimulation, the ABL and BCR genes move towards the membrane, their mutual distances increase, and the shortest distance between heterologous ABL and BCR genes increases. The distribution of the shortest distances between ABL and BCR genes in the G0 phase of lymphocytes corresponds to the theoretical distribution calculated by the Monte-Carlo simulation. Interestingly, the shortest ABL-BCR distances in G1 and S(G2) nuclei are greater in experiment as compared with theory. This result suggests the existence of a certain regularity in the gene arrangement in the G1 and S(G2) nuclei that keeps ABL and BCR genes at longer than random distances. On the other hand, in about 2% to 8% of lymphocytes, the ABL and BCR genes are very close to each other (the distance is less than approximately 0.2 to 0.3 microm). For comparison, we studied another pair of genes, c-MYC and IgH, that are critical for the induction of t(8;14) translocation that occurs in the Burkitt's lymphoma. We found that in about 8% of lymphocytes, c-MYC and IgH are very close to each other. Similar results were obtained for human fibroblasts. gamma-Radiation leads to substantial changes in the chromatin structure of stimulated lymphocytes: ABL and BCR genes are shifted to the nuclear center, and mutual ABL-BCR distances become much shorter in the G1 and S(G2) nuclei. Therefore, we hypothesize that the changes of chromatin structure in the irradiated lymphocytes might increase the probability of a translocation during G1 and S(G2) stages of the cell cycle. The fact that the genes involved in the t(8;14) translocation are also located close together in a certain fraction of cells substantiates the hypothesis that physical distance plays an important role in the processes leading to the translocations that are responsible for oncogenic transformation of cells.
Keywords: geny pro imunoglobuliny; bcr-abl fúzní proteiny; Fusion Proteins, bcr-abl; Genes, abl; fibroblasty; geny myc; Philadelphia Chromosome; Cell Nucleus; Fibroblasts; hybridizace in situ fluorescenční; lidské chromozomy, pár 8; Chromosomes, Human, Pair 8; Immunoglobulin Heavy Chains; translokace genetická; Chromosomes, Human, Pair 14; buněčné jádro; Chromosomes, Human, Pair 22; lymfocyty; Genes, Immunoglobulin; Gamma Rays; Interphase; interfáze; lidské chromozomy, pár 14; lidé; geny abl; Monte Carlo Method; lidské chromozomy, pár 9; Humans; Lymphocytes; metoda Monte Carlo; Cell Cycle; Chromosomes, Human, Pair 9; Translocation, Genetic; těžké řetězce imunoglobulinů; In Situ Hybridization, Fluorescence; buněčný cyklus; filadelfský chromozom; Genes, myc; lidské chromozomy, pár 22; záření gama